2023
DOI: 10.3389/fpsyg.2022.1049660
|View full text |Cite
|
Sign up to set email alerts
|

Authoritarianism, psychopathy, and resistance to wearing masks during the COVID-19 pandemic: A partial replication and extension of key findings

Abstract: Controversial recent research suggests Americans with more authoritarian tendencies showed less concern about COVID-19 and self-report less mask wearing. The present study set out to replicate this result with a larger sample. The study also sought to extend the original research by investigating how the Dark Triad traits of narcissism, psychopathy, and Machiavellianism are related 1 COVID-19 attitudes and behaviors. Nine-hundred ninety-six United States high school graduates were asked 8 questions about their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…callousness, COVID-19, impulsivity, motivation, personality, prevention, psychopathy Clemente, 2021;Gogola et al, 2021;Hardin et al, 2021;Hughes & Machan, 2021;Montiero et al, 2022;Nowak et al, 2020;Prichard & Turner, 2023;Triberti et al, 2021). Other studies using a two-factor (primary and secondary) assessment of psychopathy found mixed evidence of either no association of prevention behavior with primary and secondary psychopathy or negative associations with both (Blanchard et al, 2023;Zajenkowski et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…callousness, COVID-19, impulsivity, motivation, personality, prevention, psychopathy Clemente, 2021;Gogola et al, 2021;Hardin et al, 2021;Hughes & Machan, 2021;Montiero et al, 2022;Nowak et al, 2020;Prichard & Turner, 2023;Triberti et al, 2021). Other studies using a two-factor (primary and secondary) assessment of psychopathy found mixed evidence of either no association of prevention behavior with primary and secondary psychopathy or negative associations with both (Blanchard et al, 2023;Zajenkowski et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Most existing studies that investigated the relation between psychopathy and engagement in COVID‐19 prevention (and related) behavior have relied on single‐trait assessment of psychopathy embedded in a Dark Triad conceptualization of personality. Although some of these studies found no association between psychopathy and prevention behavior, most revealed a negative association (Allessandri et al., 2020; Chávez‐Ventura et al., 2022; Espinosa & Clemente, 2021; Gogola et al., 2021; Hardin et al., 2021; Hughes & Machan, 2021; Montiero et al., 2022; Nowak et al., 2020; Prichard & Turner, 2023; Triberti et al., 2021). Other studies using a two‐factor (primary and secondary) assessment of psychopathy found mixed evidence of either no association of prevention behavior with primary and secondary psychopathy or negative associations with both (Blanchard et al., 2023; Zajenkowski et al., 2020).…”
Section: Introductionmentioning
confidence: 99%